(In)visibility and the (unheard) voice of the Roma in Estonia: the depiction of Roma history and culture in museum exhibitions. Issue 1 (2nd January 2023) - Roht-Yilmaz, Eva-Liisa
ABSTRACT: The article analyzes the depiction of Roma culture and history, including Roma genocide, in Estonian museums, on the example of three recent permanent exhibitions and a traveling exhibition. Inspired by the new museology principles, I discuss the silences concerning the Roma in memory institutions together with participation possibilities for Roma NGOs. I conclude that the depiction of Roma in permanent exhibitions is influenced by the lack of research (interest) and (knowledge about) materials, which is influenced by the conflict in collective memory about World War II and by the circulation of a false narrative of Roma not being a traditional minority in Estonia.